The fragmentation of social services : factors hindering the delivery of social services to unaccompanied child migrants in Johannesburg, South Africa - Mboyisa, Natasha Zama (My University, 2014)
The situation of children who migrate without an adult dependent makes them particularly vulnerable. Inequalities in development, natural disasters, and political conflict and warfare that are characteristic of most countries today have contributed greatly to the cross border migration of children to the country with and sometimes without their parents and/ or any other form of legal adult guardianship. The Bill of Rights in the South African Constitution, Act 108 of 1996 Section 28 (1) (c) guarantees every child in the country the right to social services. Informed by the human rights-based approach, the study ventured into exploring how this right talks to the situation of unaccompanied child migrants in the country. This study focused on factors that hindered the delivery of services to unaccompanied child migrants and data was collected from nine social service provider and officials, one working at a state department and eight from five Non- Government Organizations in Johannesburg. The method of data collection used was interviews and semi- structured interview schedule was used as a data collection instrument. The data collected from the participants was analyzed using a rigorous analysis process referred to as thematic content analysis. The findings deduced from this analysis reveal that unaccompanied child migrants are exposed to various challenges when accessing social services in Johannesburg. The findings also demonstrate that the inability of unaccompanied child migrants to access social services does not have a negative impact on unaccompanied child migrants alone, but their situation has a negative impact also on the overall country’s functioning, especially on the country’s development. Continued education and training to social service providers about legal frameworks and on unaccompanied child migrants, the country’s overall political interest and will on international migration and the presence of a clear guideline to social service providers on unaccompanied child migrants, were all possible intervention strategies that participants argued would be best able to promote the right of unaccompanied child migrants to social services. Key words: social services; unaccompanied child migrants, social service providers
A report on a research project presented to The Department of Social Work School of Human and Community Development Faculty of Humanities University of the Witwatersrand In partial fulfillment of the requirements for the degree Master of Arts by Coursework and Research Report in the Field of Social Development